An investigation on photoconductivity of non-stoichiometric CuZnSn(S, Se)4 thin films for photovoltaic applications. (31st May 2019) - Hegazy, H H; Ashraf, I M; Algarni, H; Umar, Ahmad
Abstract: In this work, polycrystalline CuZnSn(S, Se)4 thin films were deposited on soda lime glass by a facile thermal evaporation method using a single source. The temperature dependence of electrical conductivity in the dark σ D and under illumination σ ph has been evaluated over 290 K–425 K. The synthesized thin films exhibit a p-type semiconductor, regardless of the zinc ratio. The electrical conductivities for all compositions increase with increasing temperature indicating semiconducting behaviour of the material, and were explained by the thermionic emission model over grain boundary barriers. The grain boundary barrier energy decreases on exposure to light and was found to vary with Zn concentration. The photoconductivity increases with light intensity and the calculations reveal that the recombination process is bimolecular in nature. The persistent photoconductivity was measured and the decay process exhibited non-exponential behaviour, and then the concept of a differential lifetime was used. The temperature dependence of the differential lifetime was studied for all films. Understanding of the current results is quite important for polycrystalline solar cell thin films.